Interactions of rice seedlings with bacteria isolated from rice roots - Prayitno, J.; Stefaniak, J.; McIver, J.; Weinman, J.J.; Dazzo, F.B.; Ladha, J.K.; Barraquio, W.; Yanni, Y.G.; Rolfe, B.G. (Commonwealth Scientific and Industrial Research Organisation, 1999)
The interactions between two groups of rice endophytic bacterial strains and several rice cultivars were investigated. Various strains of Rhizobium leguminosarum bv. trifolii, originally isolated from rice plants grown in Egypt, comprise one group. The second group of bacterial strains was isolated from rice cultivars grown in the Philippines. Inoculation experiments with rice seedlings showed that specific isolates of these rice-associating bacteria could either promote, inhibit, or have no influence on rice plant growth. Furthermore, these growth effects were greatly influenced by the environmental growth conditions used. Studies to examine root colonisation patterns, using Rhizobium strains into which a plasmid expressing the green fluorescent protein has been placed, showed that the bacteria preferentially colonise rice seedling surfaces mainly in clumps. This occurs along grooves on the rice root surface, or at the emerging lateral root zones and at the root tips. However, rhizobia could also colonise intercellularly in lateral roots formed on the main roots near the culm region of the seedling. Under the growth conditions used, this occurred most frequently with strain R4 which multiplied and migrated to form long lines of individual bacterial cells along the inside of growing lateral roots. A bioassay to measure bacterial multiplication in rice leaves showed that the rice-associating strains can multiply and survive at different rates within these tissues. They were not, however, detected migrating into other parts of the leaf from the original site of pressure-infiltration, indicating that the bacterial ability to migrate within the lateral roots is not matched by a similar capacity in rice leaves. We suggest that some of these rice-associating bacteria possess important genes that enhance their ability to intimately colonise niches on and within rice tissues, and promote rice plant growth.